Vulnerability of teleosts caught by the pelagic tuna longline fleets in South Atlantic and Western Indian Oceans. (June 2017) - Lucena-Frédou, Flávia; Kell, Laurie; Frédou, Thierry; Gaertner, Daniel; Potier, Michel; Bach, Pascal; Travassos, Paulo; Hazin, Fábio; Ménard, Frédéric
Abstract: Productivity and Susceptibility Analysis (PSA) is a methodology for evaluating the vulnerability of a stock based on its biological productivity and susceptibility to fishing. In this study, we evaluated the vulnerability of 60 stocks of tuna, billfishes and other teleosts caught by the tuna longline fleets operating in the South Atlantic and Indian Ocean using a semi-quantitative PSA. We (a) evaluated the vulnerability of the species in the study areas; (b) compared the vulnerability of target and non-target species and oceans; (c) analyzed the sensitivity of data entry; and (d) compared the results of the PSA to other fully quantitative assessment methods. Istiophoridae exhibited the highest scores for vulnerability. The top 10 species at risk were: Atlantic Istiophorus albicans ; Indian Ocean Istiompax indica; Atlantic Makaira nigricans and Thunnus alalunga ; Indian Ocean Xiphias gladius ; Atlantic T. albacares, Gempylus serpens, Ranzania laevis and X. gladius; and Indian Ocean T. alalunga . All species considered at high risk were targeted or were commercialized bycatch, except for the Atlantic G. serpens and R. laevis which were discarded, and may be considered as a false positive. Those species and others at high risk should be prioritized for further assessment and/or data collection. Most species at moderate risk were bycatch species kept for sale. Conversely, species classified at low risk were mostly discarded. Overall, species at high risk were overfished and/or subjected to overfishing. Moreover, all species considered to be within extinction risk (Critically Endangered, Endangered and Vulnerable) were in the high-risk category. The good concordance between approaches corroborates the results of our analysis. PSA is not a replacement for traditional stock assessments, where a stock is assessed at regular intervals to provide management advice. It is of importance, however, where there is uncertainty about catches and life history parameters, since it can identify species at risk, and where management action and data collection is required, e.g. for many species at high and most at moderate risk in the South Atlantic and Indian oceans.